TEMPORAL CHANGE IN ROBERT FROST’S POEM - Henriono Nugroho (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
This article concerns with a systemic stylistic analysis on a poem in terms of Systemic Functional Linguistics and Verbal Art Semiotics. The writing uses library research, qualitative data, documentary study, descriptive method and intrinsic-objective approach. The semantic analysis results in both automatized and foregrounded meanings. Then the automatized meaning produces lexical cohesion and in turn, it produces subject matter. Meanwhile, the foregrounded meaning produces the literary meaning and in turn, it creates theme. Finally, the analysis indicates that the subject matter is about the singing bird, the literary meaning is about temporal change and the theme is about natural law.